Analisis Blue Ocean Strategy Dalam Memenangkan Persaingan Bisnis Locus Abdnn Sukabumi - Alfarizi, Muhamad; Danial, R. Denny Muhammad; Nurmala, Resa (Peneliti.net, 2024)
The coffee shop in Sukabumi city continues to experience growth every year. One of the coffee shops in Sukabumi, Locus Abdnn, must be able to have the ability to create a strategy that can be used, and one strategy that needs to be implemented is by using the Blue Ocean Strategy. The aim of this research is to understand Albdnn Sukalbumi's Locus Strategy in preventing increase and stabilize sales by using the Blue Ocean Strategy. This research uses qualitative research methods with a descriptive approach. The population in this study were Locus Albdnn customers during the observation period. The sampling technique used was non-probability sampling using purposive sampling to obtain a sample of 20 informants who were selected based on certain criteria. The data collection techniques used in this research include observation, preliminary research, literature study and documentation. In testing the validity of the data, 3 types of triangulation will be carried out, namely technical trials, source trials, walkthrough trials. After the required data are prepared, the next step is to process them using a mathematical model that is in accordance with the methods used such as data reduction, data presentation and verification. From the results of the data analysis, it can be concluded that Locus Abdnn must innovate to attract consumers by improving quality by adding its own processed Indonesian coffee products so that they become distinctive and able to increase promotions through social media so that more and more local people are interested in buying products at Locus. Albdn. So, in order to increase sales profits, Locus Albdnn must be able to implement the Blue Ocean Strategy and utilize technology and innovation in the process of making instant Indonesian coffee products.